2002
DOI: 10.1590/s1413-81232002000400007
|View full text |Cite
|
Sign up to set email alerts
|

Gênero, morbidade, acesso e utilização de serviços de saúde no Brasil

Abstract: O objetivo deste trabalho é analisar o perfil de morbidade referida, acesso e uso de serviços de saúde em homens e mulheres no Brasil, segundo idade e região urbana e rural. Os dados da PNAD/98 mostram que as diferenças de gênero na morbidade variam com a idade: desfavoráveis aos meninos até os 10 anos e desfavoráveis às mulheres a partir dos 15 anos, aumentando até os 64 anos e reduzindo após esta idade. A alta prevalência de atendimento indica que as barreiras de acesso dos que procuram serviços de saúde são… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
0
308

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 441 publications
(465 citation statements)
references
References 22 publications
11
128
0
308
Order By: Relevance
“…Nonetheless, comparisons between studies should be done with caution due to differences in the criteria used to defi ne regular users, in the cultural and socioeconomic characteristics of the populations studied and in the organization of services. 13 Women perform more regular consultations, according to a Canadian study with low-income women, as also in the present study. In a context of poverty, men have long commutes to work, often far from their residence, which may limit their availability to access dental care.…”
Section: Discussionsupporting
confidence: 80%
“…Nonetheless, comparisons between studies should be done with caution due to differences in the criteria used to defi ne regular users, in the cultural and socioeconomic characteristics of the populations studied and in the organization of services. 13 Women perform more regular consultations, according to a Canadian study with low-income women, as also in the present study. In a context of poverty, men have long commutes to work, often far from their residence, which may limit their availability to access dental care.…”
Section: Discussionsupporting
confidence: 80%
“…The identification of more admissions due to PCSCs in males has been widely reported in the literature. A study in 2002 concluded that women use preventive health services more, while men are more like to use emergency services 43 . Higher alcohol and drug use and smoking are other factors that expose men to greater lifetime health risk when compared to women 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Isso pode ser visto como fruto da estratégia de descentralização que, além da ampliação no número de unidades, obedece a critérios de territorialização para sua implantação. Por outro lado, o mesmo não pode ser dito das unidades básicas tradicionais nem dos deslocamentos em busca da assistência especializada, quando foram referidos longos percursos a pé, e ainda que existisse transporte urbano, em muitos casos, a falta de dinheiro para o transporte foi fator de impedimento à utilização, como revelado em outro estudo 29 .…”
Section: Discussionunclassified